2013
DOI: 10.1017/s0007114513003838
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exposure to a cafeteria diet during gestation and after weaning on the metabolism and body weight of adult male offspring in rats

Abstract: In the present study, we investigated whether maternal exposure to a cafeteria diet affects the metabolism and body composition of offspring and whether such an exposure has a cumulative effect during the lifetime of the offspring. Female rats were fed a control (CON) or a cafeteria (CAF) diet from their own weaning to the weaning of their offspring. At 21 d of age, male offspring were divided into four groups by diet during gestation and after weaning (CON-CON, CON-CAF, CAF-CON and CAF-CAF). Blood was collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 51 publications
2
15
1
1
Order By: Relevance
“…Many studies have attempted to investigate the influence of maternal cafeteria diet on plasma glucose, insulin, triglyceride and total cholesterol levels. Some have found no differences in glucose and insulin ( Crew, Waddell & Mark, 2016 ; Crew et al, 2018 ), triglyceride ( Mucellini et al, 2014 ) and total cholesterol ( Jacobs et al, 2014 ) concentrations as observed in the present study, while others have reported higher glucose and insulin ( Holemans et al, 2004 ; Bouanane et al, 2009 ) cholesterol ( Mucellini et al, 2014 ) and triglyceride ( Chen et al, 2008 ) concentrations in cafeteria fed dams. The above-cited studies have some differences in the duration and timing of intervention.…”
Section: Discussioncontrasting
confidence: 81%
“…Many studies have attempted to investigate the influence of maternal cafeteria diet on plasma glucose, insulin, triglyceride and total cholesterol levels. Some have found no differences in glucose and insulin ( Crew, Waddell & Mark, 2016 ; Crew et al, 2018 ), triglyceride ( Mucellini et al, 2014 ) and total cholesterol ( Jacobs et al, 2014 ) concentrations as observed in the present study, while others have reported higher glucose and insulin ( Holemans et al, 2004 ; Bouanane et al, 2009 ) cholesterol ( Mucellini et al, 2014 ) and triglyceride ( Chen et al, 2008 ) concentrations in cafeteria fed dams. The above-cited studies have some differences in the duration and timing of intervention.…”
Section: Discussioncontrasting
confidence: 81%
“…It consists of a variety of products, which are characterized by good taste with high energy density with about 45–55% of the energy coming from fats 3 5 . Among the commonly used ingredients in this diet there are: biscuits, potato chips, peanut butter, chocolate, chocolate bars, cheese, sausage, jam, muffins, cakes, dried fruit 3 , 5 , 6 . CAF diet very well mimics “fast-food meals” popular among people 7 .…”
Section: Introductionmentioning
confidence: 99%
“…In six studies, maternal high fat diet protected against the adverse effects of a postnatal Western-type diet with regard to weight gain (Couvreur et al, 2011; Ferezou-Viala et al, 2007; Howie et al, 2009; Mucellini et al, 2014), insulin sensitivity (Ferezou-Viala et al, 2007; Mucellini et al, 2014), lipid levels (Shankar et al, 2008), or blood pressure (Elahi et al, 2009). The potential explanations for these unexpected findings include impacts of maternal obesity on energy homeostasis regulated by the liver and the hypothalamus (Brenseke et al, 2015; Couvreur et al, 2011); nevertheless these studies may be regarded as outliers with no known explanation.…”
Section: Introductionmentioning
confidence: 99%